Structural Interactions And Fermentation Of Lentil Protein With Other Proteins To Improve The Functional And Nutritional Properties - Mohammad Hani Ahmad, Alrosan (2022)
In recent years, there has been increasing interest in plant-based proteins such as lentil proteins (LPs) due to their good availability, low cost, and global production. The main factors limiting the use of lentil proteins in the food industry are its low water solubility, poor digestibility, and high amount of saponins, which leads to bitterness. Protein-protein interactions (PPI) and fermentation have been used in the past to address some of these limitations in plant-based proteins. Protein complexation and WKS fermentation procedures were combined successfully to improve the functional and nutritional aspects of LP-based protein complexes.